The Role of the Code of Ethics and Code of Conduct in Maintaining the Honor and Dignity of Judges - Lubis, Andi Hakim; Zulyadi, Rizkan; Pinem, Serimin; Siagian, Fahrizal S.; Muazzul, Muazzul (Universitas Muhammadiyah Surakarta, 2024)
The public has high expectations of judges and the judicial system, given that the judiciary is an institution authorized to decide cases and provide justice. However, in recent years, the public has been watching the behavior of judges and the quality of their decisions in adjudicating cases. Not a few judges' decisions invite criticism and cynicism, lead to public distrust, and form a considerable skepticism towards the judiciary. The research method used is normative legal research. This research is descriptive analytical. The data collection technique was carried out by means of literature study. The result of the research is that the role of ethical guidelines and judge behavior is needed in order to maintain and uphold the honor and dignity, as well as the behavior of judges. The code of ethics and behavior of judges is the core inherent in the profession of judges containing ethical and moral values, to realize a court that has good authority and dignity. Obstacles arise from within the judiciary itself, especially in relation to the lack of effective internal supervision, and the tendency to increase various forms of abuse of authority by judges. The implementation of the Code of Ethics and Code of Conduct for Judges must be carried out effectively without interference from various parties with interests. So as to be able to maintain the dignity, honor and nobility of the judicial profession. Masyarakat memiliki ekspektasi yang tinggi terhadap hakim dan sistem peradilan, mengingat peradilan adalah lembaga yang berwenang untuk memutuskan perkara dan memberikan keadilan. Namun, dalam beberapa tahun terakhir, publik mencermati perilaku hakim dan kualitas putusannya dalam mengadili perkara. Tidak sedikit putusan hakim yang mengundang kritik dan sinisme, menimbulkan ketidakpercayaan masyarakat, dan membentuk skeptisisme yang cukup besar terhadap lembaga peradilan. Metode penelitian yang digunakan adalah penelitian hukum normatif. Penelitian ini bersifat deskriptif analitis. Teknik pengumpulan data dilakukan dengan cara studi kepustakaan. Hasil penelitian ini adalah peran pedoman etika dan perilaku hakim sangat diperlukan dalam rangka menjaga dan menegakkan kehormatan dan keluhuran martabat serta perilaku hakim. Kode etik dan perilaku hakim merupakan inti yang melekat pada profesi hakim yang mengandung nilai-nilai etika dan moral, untuk mewujudkan peradilan yang berwibawa dan bermartabat. Hambatan muncul dari internal lembaga peradilan sendiri, terutama terkait dengan belum efektifnya pengawasan internal dan kecenderungan meningkatnya berbagai bentuk penyalahgunaan wewenang oleh hakim. Penerapan Kode Etik dan Pedoman Perilaku Hakim harus dilakukan secara efektif tanpa adanya campur tangan dari berbagai pihak yang memiliki kepentingan. Sehingga mampu menjaga keluhuran martabat, kehormatan dan keluhuran profesi hakim.